A correlational study of the personality of PGH nurses and their leadership readiness - Carpio, Gian Carlo A.; Ching, Carla I.; Jacla, Frel E.; Pancho, John Stuart R.; Ramirez, Kathleen Ann G.; Sison, Abigail T.
With the advent of the migration of competent nurses who were leading the nursing profession, the health care organizational system undergoes drastic changes. Some of these changes include understaffing, high turnover rate, and decreased patient satisfaction, which consequently compromise the quality of nursing care. In response to these issues, institutions attempt to fill up the posts vacated by the nurse leaders without much consideration on the standard qualification required for a position. Staff nurses become obliged to perform managerial skills to augment the need for nurse leaders in the clinical areas, In line with this, the study has been made to look into the personality of the general nursing staff and correlate it with their readiness to assume managerial position. The study aimed to correlate the personality type of PGH nurses and their leadership readiness. The alternative hypothesis of the study is stated that there is an association between personality of the PGH nurses and their leadership readiness. Among its objectives are as follows: To determine the personality type of N-I and N-II nurses of the Philippine General Hospital nurses To define leadership readiness of N-I and N-II in the context of the roles they assumed in the PGH setting To evaluate the leadership readiness of N-I and N-II of PGH. To correlate the personality of N-I and N-II of PGH and their readiness to assume leadership position To identify other factors that may influence leadership readiness of N-I and N-II PGH nurses. The study utilized the descriptive-correlational research design to describe the relationship of the personality of the nurses in the Philippine General Hospital and their leadership potential. Samples were computed using the multistage sampling procedure. The target population involved the registered nurscs of Philippine General Hospital occupying Nurse 1 (N-1) and Nurse 2 (N-2) positions. They were chosen as the participants mainly because they would soon assume the managerial positions as the institution copes with the vacancies and because their readiness to assume these are to be evaluated. The setting of the study was confined to the Philippine General Hospital as one of the premier institution delivering quality health care. Consent was obtained prior to data-collection. Confidentiality was also observed by assigning code numbers to questionnaires and privacy was ensured by keeping the informants’ answers undisclosed to others. Three methods of data collection were utilized namely key informant interview, review of literature and questionnaires. The ROL and interview with some of the head of nursing services in PGH were done to determine the definition of leadership readiness. The Enneagram checklist-type questionnaire was ud to determine the types of personality of the nurses. There were 9 possible types and they were grouped into three triads namely: Instinctive, Feeling and Thinking personality triads. The leadership readiness of the subjects was measured using the Performance Rating Scale (PES). Data collected were analyzed via descriptive and nonparametric statistics. Central tendencies of the sociodemographic factors: age and work experience and the ratio of the sociodemographic factors: sex, marital status, education, achievements, support availability, life events and effect of personality of the actual subjects were used. Chi-square test was utilized to interpret the association of the independent variable, personality, and the dependent variable, leadership readiness. Chi-square test was employed since two sets of data were derived from the same subject of nominal measurement. The test was done with the level of significance set at a = 0.05. The subjects who were all graduates of Bachelor of Science in Nursing had a range of 21 to 37 years of age. Majority of them were female (76%). The work experience ranges from 0.08 to 11 years. Many of them come from a nuclear family (56%). Emotional, financial, and social support were all present to 61% of the respondents, One to three types of life events were experienced by 76% of them. The data gathered showed that majority of the subjects belong to the thinking personality triad or those that have the enthusiast, investigator and loyalist type of personality. Majority of the nurses already possess leadership readiness (79%). The chis square test revealed that the thinking personality triad is associated with leadership readiness while the feeling and Instinctive personality did not qualify to show an association. In conclusion, it was found out that N-I and N-II PGH nurses possessed the enthusiast type of personality or the spontaneous, distractible, versatile and scattered type. In the same way, the thinking triad where the said personality type belongs gained the most number of subjects possessing it. Leadership readiness in PGH setting is one’s ability to accept the responsibilities and duties associated with being a leader in the context of six components: patient care, human resource management, unit care, teaching, research and linkages. Majority of the subjects (79%) possessed leadership readiness based on the evaluation of their supervisors. This implies that N-I and N-II nurses are ready to assume the duties and responsibilities of higher positions specifically being charge nurses. There is enough evidence to say that an association exists between the thinking personality triad and leadership readiness. This means that nurses that pose the characteristics that try to cope up with their dominant feeling, which is anxiety, tend to be the ones who are ready To assume leadership roles and responsibilities. On the other hand, the instinctive and feeling personality triads did not gain sufficient evidence to show an existing association between these two and leadership readiness. This may be due to the limited sample size, thus certain recommendations are made. Certain factors may have influenced the leadership readiness and personality of the nurses such as age, sex, family structure, educational attainment, experiences, and life events.